Old Roads New Highways : Fifty Years of Pakistan - Schofield, Victoria (Karachi Oxford University Press, 1997)
This collection brings together the insights of a wide range of writers who examine Pakistan's development in its varied yet interconnected spheres since its creation in 1947. Topics covered include the arts and drama as they try to survive alongside a sharp trend towards Islamic fundamentalism, schools as they attempt to meet the demand of an ever increasing population, and democracy as it struggles to establish itself in a country prone to military dictatorship.
Include Index
Keywords: Social Conditions -- Civilization -- Economic History